Irrigation governance, private investment, and agricultural productivity in India - Kumar, Anjani; Bathla, Seema; Elumalai, K.; Saroj, Sunil (International Association of Agricultural Economists, 2021)
This paper analyzes the correlation of irrigation investments among agricultural households across India’s 20 major states with irrigation governance and agricultural productivity. A governance index is constructed based on select indicators that capture important dimensions of irrigation water governance. These dimensions include irrigation management, farmers’ participation, accountability, and sustainable use. Using principal component analysis, the index is constructed for each of the selected states for the period 2001/2002 to 2015/2016. Results reveal that in some states farmers’ dependence on electric tube wells, and hence groundwater, has increased extensively due to inadequate access to public (canal) irrigation. Irrigation accounted for 35 percent of the total investments undertaken by farmers, with little increase between 2002/2003 and 2012/2013. Over that period, there was an increase in farmers’ expenditures on machinery, tractors, and livestock. Results further indicate that good governance has a positive influence on private investment in agriculture, which in turn can contribute to enhanced productivity and an increase in farmers’ incomes. This argument is supported by the results obtained from a structural equation model and from ICAR–ICRISAT household, individual, and plot-level data. This suggests that states where both governance and private investment in irrigation are at very low levels should receive higher priority; these include Assam, Odisha, West Bengal, Kerala, Bihar and Jharkhand, and Uttar Pradesh and Uttarakhand. Other states which are low in governance but high in irrigation investment (Madhya Pradesh, Chhattisgarh, Himachal Pradesh, and Karnataka) should improve governance in order to enable efficient use of irrigation resources.